SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN EKSTRAKURIKULER ATLETIK BERDASARKAN BAKAT SISWA MENGGUNAKAN METODE PROFILE MATCHING (STUDI KASUS : SMP NEGERI 17 KOTA CIREBON) - Agnes Basuki; Petrus Sokibi; Tiara Eka Putri (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2021)
Athletic achievements at SMP Negeri 17 Cirebon City must be maintained by continuing to explore and look for students who have potential and talent in athletic from year to year through extracurricular activities. However regarding this matter, it is not easy for the school to determine which athletic branch is in accordance with the talents of the students. The process of determining student athletic is carried out through the results of each student's test. The test results tend to be less objective because there are no other supporting factors. Therefore, a system is needed that can be used as a search and determination of student athletic talent. Decision Support Systems can be a solution to make it easier to determine student athletic. With this system, it is hoped that it can provide information on the results of determining athletic extracurricular activities objectively. This study applies the Profile Matching method to determine student athletic extracurriculars, and the system is made in the PHP programming language and SQL database using MySQL. At the system design stage, it is described using UML diagrams. The final result of this study obtained the results of determining the student's athletic extracurricular branch with the percentage of manual calculation results compared to the results of the system calculation there is a match of 100%.